Evaluation of the in vitro and in vivo anti-inflammatory activity of Gymnosporia montana (Roth). Benth leaves. (28th October 2022) - Ambati, Goutami G.; Yadav, Kamalender; Maurya, Ruchika; Kondepudi, K.K.; Bishnoi, Mahendra; Jachak, Sanjay M.
Abstract: Ethno-pharmacological relevance: Gymnosporia montana (Roth) Benth an herbaceous shrub used in Indian traditional medicine their leaves decoction was used as mouthwash to get relieve from toothache, hence it is also known as Dantakashta in Sanskrit language which means the plant used for tooth problems. Traditionally the leaves juice used to alleviate inflammation and in some parts of India like Saurashtra in Gujarat, leaves were chewed as a folklore cure for Jaundice and in Bhandra region Karnataka, leaves extract mixed with cow milk used for jaundice. Hepatoprotective activity for G. montana leaves was well reported however, its use for inflammation and toothache are still not studied to investigate active phytoconstituents responsible for anti-inflammatory activity. Aim of the study: The present study aimed at bioactivity guided isolation of G. montana leaves extracts using inhibition of pro-inflammatory mediators such as nitric oxide (NO), tumor necrosis factor (TNF-α), and interleukins (IL-1 β and IL-6) in RAW 264.7 cells in vitro assay to yield bioactive phytoconstituents. Materials and methods: The n-hexane, ethyl acetate and methanol extracts prepared from G. montana leaves were evaluated for cell viability using MTT assay. The effect of extracts to inhibit the pro-inflammatory mediators like NO, TNF-α, IL-1 β and IL-6 in RAW 264.7 macrophages was measured by enzyme-linked immunosorbent assay (ELISA). The quantitative analysis of the isolated phytoconstituents was performed using quantitative Nuclear Magnetic Resonance (qNMR). Results: The n-hexane, ethyl acetate, and methanol extracts of G. montana leaves exhibited cell viability in the range of 97.43–84.88% at 50 μg/mL concentration in RAW 264.7 macrophages. In-vitro evaluation of extracts showed that n-hexane extract was most effective in inhibiting NO, TNF- α, IL-1 β and IL-6 inflammatory mediators at 50 μg/mL in lipopolysaccharides (LPS) stimulated RAW 264.7 cells. Further n-hexane extract, its fraction GMHA3 and β -amyrin exhibited significant anti-inflammatory activity at 100, 50 and 30 mg/kg per oral, respectively in carrageenan-induced rat paw edema. The quantitative analysis by qNMR revealed β -amyrin as a major compound in the n-hexane extract. Conclusions: In vitro and in vivo bioassay results suggested that G. montana n-hexane extract, its fraction GMHA3 and β -amyrin exhibits significant anti-inflammatory activity proves the traditional uses of G. montana leaves. The reported activity of β -amyrin for periodontitis provides evidence of profound the use of G. montana leaves for toothache and anti-inflammatory activity. Graphical abstract: Image 1